Fabrication and biological evaluation of chitosan coated hyaluronic acid-docetaxel conjugate nanoparticles in CD44+ cancer cells. Issue 1 (December 2016) - Shabani Ravari, Nazanin; Goodarzi, Navid; Alvandifar, Farhad; Amini, Mohsen; Souri, Effat; Khoshayand, Mohammad; Hadavand Mirzaie, Zahra; Atyabi, Fatemeh; Dinarvand, Rassoul
Abstract Background Hyaluronic acid (HA) has been used for target-specific drug delivery because of strong affinity to CD44, a marker in which overexpressed in cancer cells and cancer stem cells. Conjugation of HA to the cytotoxic agents via active targeting can improve efficacy, biodistribution, and water solubility. To be able to benefit from passive targeting as well, a nanoparticulate system by counter ion using a polycation like chitosan may lead to a perfect delivery system. Methods Water soluble Hyaluronic acid-Docetaxel (HA-DTX) conjugate was prepared and used to formulate chitosan-coated HA-DTX nanoparticles by polyelectrolyte complex (PEC) method and optimized using Box-Behnken design. Biological evaluation of nanoparticles was done in CD44+ cancer cells. Results and discussion Biological evaluation of optimized formula showed IC50 of nanoparticles for 4 T1 and MCF-7 cell lines were 45.34 μM and 354.25 μM against 233.8 μM and 625.9 μM for DTX, respectively with increased cellular uptake showed by inverted confocal microscope. Conclusion Chitosan-coated HA-DTX nanoparticles were more effective against CD44+ cells than free DTX. Graphical abstract Chitosan coated hyaluronic acid-docetaxel conjugate nanoparticles fabricated and evaluated in CD44+ cancer cells